CHALLENGING TIMES FOR POWER PLANTS - Mesarović, Miodrag M (Termotehnika, 2017)
Power plants face today, and will continue so in the future, a variety of challenges, along with many uncertainties as well. Overshadowed by an inevitable and burdensome transition to a low carbon economy as the most exploited subject, there are also numerous issues, often overseen or even neglected, that may make position of power plants critical with respect to the security of supply, particularly when considering a massive move of mobility towards electric drives or a high penetration of intermittent renewables, for example. Exposed to a brutal and often unfair competition with subsidized players on the open market, some power plants are being economically and/or politically disqualified by ones based on another kind of primary energy sources. Addressed briefly are the above and some other issues, including water-energy nexus, energy storage, clean coal and CCS technologies, decentralized generation, role of virtual power plants, smart networking, cyber threats, as well as energy price volatility, global recession, geopolitical concerns, cross-border cooperation, climate deal, strong or smart solutions for security of energy supply, and some other dilemmas, challenges and/or uncertainties attributed to power plants in the times to come.